Ulcerative colitis: STRIDE-ing beyond symptoms with new standards - Shu Wen Tay; Kevin Kim Jun Teh; Tiing-Leong Ang; Malcolm Tan (Singapore Medical Journal)
The landscape of ulcerative colitis has changed in the last two decades. Advancements in pharmacotherapeutics have heralded the introduction of new treatment options, with many agents in development. Better clinical outcomes are seen with tighter disease control, made possible with greater understanding of inflammatory pathways and their blockade with drugs. There has been a resultant shift in treatment targets, beyond symptoms to endoscopic and histological healing. Controlling the burden of disease activity also lowers the risk of developing colorectal cancer. Colorectal cancer screening now requires the use of dye-based agents and high-definition colonoscopy to improve the detection of colonic neoplasms.